The ‘Cervuli’ and ‘Anniculae’ in Caesarius of Arles - Arbesmann, Rudolph (Traditio, 1979)
Two passages in the sermons of Bishop Caesarius of Arles († 542) have aroused the special interest of philologists and students of the history of religion alike. The first passage is found in the concluding section of a sermon in which the bishop scathingly criticizes some superstitions and heathen customs which, to all appearances, were still rife among the common people of his day.